STRATEGI KOMUNIKASI PUBLIK HUMAS DALAM MEMBANGUN HUBUNGAN DENGAN MASYARAKAT (STUDI PADA DINAS KOMUNIKASI DAN INFORMATIKA BIDANG INFORMASI DAN KOMUNIKASI PUB;IK DI KABUPATEN OGAN KOMERING ULU) - Shava Verellia, Melanie; Eraskaita Ginting (Program Studi Komunikasi dan Penyiaran Islam, 2025)
This study examines the public communication strategy established by the Ogan Komering Ulu Regency Communication and Information Service to build effective relationships with the community. Using a qualitative research paradigm, this study applies purposive sampling to select key informants including employees directly involved in the public communication strategy. Data were collected through in-depth interviews, document studies, and direct observation of communication activities. At the data analysis stage, it refers to the two-way symmetrical theory according to James Grunig which states two-way communication. The findings show that adjusting communication strategies to local cultural factors significantly increases message acceptance among the community. This study emphasizes the importance of openness and accessibility of information in building public trust and participation in government. Finally, this study highlights the need to improve digital literacy among the community to bridge the information gap between the government and the public.